Analisis Perilaku Kesadaran Privasi Data Pengguna Sistem Informasi Akademik dengan Pendekatan Technology Threat Avoidance Theory - Hamdi, Yusrizal; Gunawan, Catur Eri; Putra, Imamulhakim Syahid (TIN: Terapan Informatika Nusantara, 2025)
The implementation of the Sistem Informasi Akademik (SIMAK) has raised concerns regarding data security, particularly the privacy of personal data, academic grades, and Kartu Rencana Studi (KRS) information. Threats to user data privacy often originate from internal actors, posing risks to the confidentiality, integrity, and availability of information. This study aims to explore the factors influencing SIMAK users’ privacy awareness behavior in response to such threats, using the Technology Threat Avoidance Theory (TTAT) as a theoretical framework. A quantitative research approach was employed, with data collected through questionnaires distributed to 393 respondents, comprising active SIMAK users from both student and faculty groups. The collected data were analyzed using the Covariance-Based Structural Equation Modeling (CB-SEM) method with the SmartPLS 4 software. The results reveal that perceptions of vulnerability and severity, as well as their interaction, positively influence threat perception. This perceived threat significantly enhances the motivation to avoid risks. However, the interaction between threat perception and safeguard effectiveness shows a negative impact. On the other hand, self-efficacy positively contributes to avoidance motivation, which in turn influences users’ awareness behavior in protecting data privacy. These findings emphasize the importance of enhancing individual awareness and capability in maintaining information security within academic information systems.